The Ethics of the Early Wittgenstein and the Debates of Fin-de-Siècle Vienna: Neither Beyond nor Within the World - Quintana Paz, Miguel Ángel (Scenari, 2022)
If we classify ethical theories into ‘immanentist’ (those that detect what is ethically acceptable in some type of world events, such as the utilitarian growth of general benefits) and ‘transcendentalist’ (those that locate in some space beyond this world the reason why we should behave ethically – for example, due to some kind of otherworldly reward –), then the moral philosophy of the so-called ‘first’ Wittgenstein would occupy a special place between both extremes of such a dichotomy. To a certain extent, it could be said that the ethical proposal of Wittgenstein during his years composing the Tractatus Logico-philosophicus maintains a delicate balance that avoids both its exclusive submission to transcendental instances (fundamentals), and its total assimilation by immanent motivations (benefits) when justifying the fact of acting in a correct way. In this article we will look at such a Wittgensteinian pirouette between both members of the transcendent-immanent dualism, and we will suggest that the peculiar place where he leaves ethics, between the heavenly and the earthly, may not be completely alien to some thesis of the Christian religion.